Pengaruh Pendidikan Terhadap Partisipasi Wanita Bekerja di Indonesia - Nur Azlin Syafika; Joan Marta (Universitas Negeri Padang, 2025)
Female labor force participation in Indonesia is influenced by various factors, including education level, marital status, age, and residential area. This research aims to analyze the effect of education on female labor force participation in Indonesia using multiple logistic regression analysis with data from SAKERNAS 2020. The results show that Diploma and Bachelor's degree graduates have higher employment opportunities compared to those with junior high school education or lower, while high school graduates actually have lower opportunities. Higher education increases the chances of working in the formal sector but decreases opportunities in the non-formal sector. Other factors such as marital status, age, and residential area also significantly influence women's labor participation. Improving access to education and implementing labor policies that support work flexibility are recommended to increase female labor force participation in Indonesia.